Ontology-based data integration in EPNet: production and distribution of food during the Roman Empire - Calvanese, Diego; Liuzzo, Pietro Maria; Mosca, Alessandro; Remesal, José; Rezk, Martin; Rull, Guillem (Engineering applications of artificial intelligence, 2016)
Semantic technologies are rapidly changing the historical research. Over the last decades, an immense amount of new quantifiable data have been accumulated, and made available in interchangeable formats, in social sciences and humanities, opening up new possibilities for solving old questions and posing new ones. This paper introduces a framework that eases the access of scholars to historical and cultural data about food production and commercial trade system during the Roman Empire, distributed across different data sources. The proposed approach relies on the Ontology-Based Data Access (OBDA) paradigm, where the different datasets are virtually integrated by a conceptual layer (an ontology) that provides to the user a clear point of access and a unified and unambiguous conceptual view.